Evaluation the Role of Vitamin C in the IUI-Treatment of Female Infertility - Batool Abdulwahid Hashim; Basima Shamkhi Al-Ghazali (Kufa Journal for Nursing Sciences)
Background: the prevalence of female infertility ranges between 7% to 28% depending on the age of the woman, however ovulatory disorder can be seen in fifths of infertile women. In a healthy body, ROS (Reactive Oxygen Species) and antioxidants remain in balance, when the balance is disrupted towards an overabundance of ROS; Oxidative stress (OS) occurs. Oxidative stress markers have been localized in follicular fluid of subfertile women undergoing assisted reproduction, Low intrafollicular oxygenation has been associated with decreased oocyte developmental potential. Vitamin C (ascorbic acid) is required for the synthesis of collagen, for the synthesis of steroid and peptide hormones, and it protects tissues of oxidative damage. There is an abundance of ascorbic acid in the ovary, which is consistent with its known roles in hormone synthesis and synergism with neurotransmitters in stimulating hormone secretion.